2003
DOI: 10.1016/s0399-1784(03)00052-5
|View full text |Cite
|
Sign up to set email alerts
|

Organic micropollutants (PAHs, PCBs, pesticides) in seaweeds of the lagoon of Venice

Abstract: Samples of seven genera of seaweeds (Ulva, Gracilaria, Porphyra, Grateloupia, Undaria, Fucus and Cystoseira), which can be used as environmental biomonitors and in several applications like human alimentation, animal feeding and cosmetics, were collected in four sampling sites in the Lagoon of Venice in spring and autumn 1999 with the aim of determining the contamination due to organic micropollutants (polychlorinated biphenyls, PCBs; chlorinated pesticides; polycyclic aromatic hydrocarbons, PAHs). On an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 24 publications
3
38
3
Order By: Relevance
“…3) in coarse and well oxygenated sediments. Exceptionally, a new population was found also in the inner part of the northern basin in an area where this species has never been found before, which confirms the strong changes that have affected the lagoon during the last 15 years (Facca et al, 2002a, b;Sfriso et al, 2003;Pavoni et al, 2003;Secco et al, 2005).…”
Section: Macroalgaesupporting
confidence: 66%
“…3) in coarse and well oxygenated sediments. Exceptionally, a new population was found also in the inner part of the northern basin in an area where this species has never been found before, which confirms the strong changes that have affected the lagoon during the last 15 years (Facca et al, 2002a, b;Sfriso et al, 2003;Pavoni et al, 2003;Secco et al, 2005).…”
Section: Macroalgaesupporting
confidence: 66%
“…In the Venice lagoon, Pavoni et al (2003) found concentrations below 10 mg/g dry weight (average concentrations) of PAHs (mainly tri-, tetra-aromatic compounds) in seaweed. Gianguzza and Orecchio (2006) examine PAHs in different Sicilian coastal environments.…”
Section: Resultsmentioning
confidence: 91%
“…Pavoni et al (2003) studied organic micropollutants, including PAH, in Venice Lagoon. These investigators found that U. pinnatifida was characterized by a greater PAH concentration than other seaweed species, and argued that this is because U. pinnatifida floated partially in a film enriched with PAH during low tides and because its mucilaginous surface is able to easily take pollutants.…”
Section: Aromatic Hydrocarbonsmentioning
confidence: 99%
“…However, due to its known ability to accumulate pollutants (Almela et al 2006;Pavoni et al 2003;Yamada et al 2007), not only its quality but also its human health safety are of interest when assessing its potential use as food. From a legislative point of view, France, the United States, New Zealand, and Australia have established specific regulations for the use of edible seaweeds in human diet (Almela et al 2006;Rupérez and Saura-Calixto 2001).…”
mentioning
confidence: 99%